Agensi Pedagogis Guru dalam Mendorong Motivasi Belajar Bahasa Arab di Sekolah Dasar - Binti Khoirunnisa, Dewi; Ahmadi, Ahmadi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2024)
This study aims to analyze the pedagogical agency of teachers in fostering elementary school students’ motivation to learn Arabic. Learning motivation is a non-intellectual psychological factor that significantly influences academic success, particularly in Arabic as a foreign language, which poses unique challenges for young learners. The study employed a descriptive qualitative approach with data collection techniques including observation, interviews, and focus group discussions (FGDs). The informants consisted of school principals, Arabic language teachers, and third-grade students at SDIIC Pacitan. The findings reveal that Arabic teachers act as motivators, facilitators, mediators, and innovators in the learning process. These roles are manifested through creating enjoyable learning environments, integrating spiritual values into Arabic instruction, providing engaging learning media, and implementing innovative teaching methods tailored to students' needs. The teachers’ pedagogical agency was proven to significantly enhance students’ motivation to learn Arabic. This study highlights the crucial role of active teacher engagement in cultivating learning motivation in Arabic language instruction at the elementary level.